ATM‐CHK2‐Beclin 1 axis promotes autophagy to maintain ROS homeostasis under oxidative stress - Guo, Qi‐Qiang (EMBO J, 2020)
The homeostatic link between oxidative stress and autophagy plays an important role in cellular responses to a wide variety of physiological and pathological conditions. However, the regulatory pathway and outcomes remain incompletely understood. Here, we show that reactive oxygen species (ROS) function as signaling molecules that regulate autophagy through ataxia‐telangiectasia mutated (ATM) and cell cycle checkpoint kinase 2 (CHK2), a DNA damage response (DDR) pathway activated during metabolic and hypoxic stress. We report that CHK2 binds to and phosphorylates Beclin 1 at Ser90/Ser93, thereby impairing Beclin 1‐Bcl‐2 autophagy‐regulatory complex formation in a ROS‐dependent fashion. We further demonstrate that CHK2‐mediated autophagy has an unexpected role in reducing ROS levels via the removal of damaged mitochondria, which is required for cell survival under stress conditions. Finally, CHK2(−/−) mice display aggravated infarct phenotypes and reduced Beclin 1 p‐Ser90/Ser93 in a cerebral stroke model, suggesting an in vivo role of CHK2‐induced autophagy in cell survival. Taken together, these results indicate that the ROS‐ATM‐CHK2‐Beclin 1‐autophagy axis serves as a physiological adaptation pathway that protects cells exposed to pathological conditions from stress‐induced tissue damage.